THE PREFERENCE OF MUSLIM HOUSEHOLDS IN CHOOSING HALAL FOOD AT PALU CITY - Sofyan, Syaakir (Journal of Sharia Economics, 2023)
Halal food products circulating in Indonesia vary greatly in terms of variety, price, and quality. The choice of food products has a significant impact on health. This study aims to understand and analyze the factors that influence the preferences of Muslim housewives to choose halal food in Palu City. This type of research is field using quantitative descriptive method with simple random sampling with a sample size of 99 selected respondents. The research findings highlight the variables of religiosity, income, and education affect the preferences of Muslim housewives to choose halal food products, while age has no effect. The results of this study are religiosity, age, income, and education affect both partially and simultaneously on the preferences of Muslim housewives choosing food. The most dominant factor is education because education provides a basis for knowledge about food selection and provides an understanding of the implications for health so that education forms a frame of mind that makes health a major consideration in choosing food.